Sustainability in Remanufacturing Operations (EcoProduction, Environmental Issues in Logistics and Manufacturing,, 2018)
The present customers' consumption models result in an increasing number of used products that need to be collected and reused or disposed. Remanufacturing is a favourable scenario in order to recover the end-of-use products. It allows to capture substantial part of the resources which were used in the primary production at lower cost, providing economic, environmental and social benefits. The book presents the methods, models, case studies for improvement of sustainability in remanufacturing facilities. The focus is on small- and medium-sized enterprises and their challenges to meet resource-efficiency goal.